Obesity-Modified CD4+ T-Cells Promote an Epithelial-Mesenchymal Transition Phenotype in Prostate Cancer Cells. (7th February 2022) - De Angulo, Alejandra; Travis, Peyton; Galvan, Gloria Cecilia; Jolly, Christopher; deGraffenried, Linda
Abstract: Obesity is associated with low-grade chronic inflammation, and metabolic dysregulation. Evidence shows that chronic inflammation inhibits protective immunity mediated by CD4+ T cells. Additionally, obesity-induced inflammation affects prostate cancer progression. However, the effect of obesity on CD4+ T-cell- response to prostate cancer is not well understood. To investigate whether obesity induces changes in CD4+ T cell cytokine profile, cytokine expression was measured in splenic CD4+ T-cells from 10-week-old male C57Bl/6 mice exposed to conditioned media (CM) from macrophages grown in sera from obese subjects. Additionally, expression levels of key regulators of Epithelial-Mesenchymal Transition (EMT) were measure in prostate cancer epithelial cells exposed to conditioned media from obesity-modified T-cells. Cell migration and invasion was measured in prostate cancer epithelial cells exposed to CM from obesity-modified CD4+ T-cells. Obesity suppressed the expression of IFNγ and IL-2 in CD4+ T-cells but up-regulated the expression of IL-6. Prostate epithelial cancer cells exposed to conditioned media from obesity-modified T cell increased the expression of EMT markers and showed a higher invasive and migratory capacity.